Clinical characteristics, anti-SARS-CoV-2 IgG titers, and inflammatory markers in individuals with post-COVID-19 condition in Kenya: a cross-sectional study - Theuri, Martin; Ndombi, Eric M.; Thamaini, Peris; Ogutu, James Opiyo; Onsongo, Lister; Madete, June K.; Ofula, Victor; Gitau, Samuel; Mwangi, Gladys; Okemo, Paul (PeerJ, 2024)
Background Post-coronavirus disease 2019 (post-COVID-19) is associated with considerable morbidity and reduced quality of life. However, studies characterizing the post-COVID-19 condition in Kenya are limited. This study aimed to determine the prevalence of post-COVID-19 condition and determine the clinical characteristics, anti-SARS-CoV-2 IgG titers, and concentrations of inflammatory markers of individuals with post-COVID-19 condition in Kenya. Methods This descriptive cross-sectional study was conducted at the Kenyatta University Health Unit, Kenya. Demographic and clinical data were collected using a questionnaire. The serum levels of anti-SARS-CoV-2 antibodies, interleukin 6 (IL-6), and C-reactive protein (CRP) were quantified by enzyme-linked immunosorbent assays. Independent samples t-test was used to compare the anti-SARS-CoV-2 IgG, IL-6, and CRP levels between the participants with and without post-COVID-19 symptoms. The case definition for post-COVID-19 condition was persistence of acute COVID-19 symptoms or emergence of new symptoms 3 months after COVID-19 diagnosis, symptoms lasting for ≥2 months, and absence of any other etiological basis to explain the symptoms. Results A total of 189 volunteers were recruited in this study (median age: 21 years, range: 18–71 years; male, 49.2%). Forty participants reported having had at least one COVID-19 positive diagnosis in the past, of which 12 (30%) complained of post-COVID-19 symptoms. Significant differences in the number and duration of symptoms were observed between the individuals with and without post-COVID-19 symptoms (t-statistic = 2.87, p = 0.01; t-statistic = 2.39, p = 0.02, respectively). However, no significant differences in serum levels of anti-SARS-CoV-2 IgG, IL-6, and CRP were observed between the two groups (P = 0.08, 0.9, and 0.28, respectively). Conclusion These findings suggest that post-COVID-19 condition is a health concern even for a relatively young population in Kenya and globally. This condition requires more attention and well-designed studies to better define it and identify clinical chemistry markers that can be used for its diagnosis.
Keywords: COVID-19; Post-COVID-19; Clinical characteristics; Inflammatory markers; Anti-SARS-CoV-2 IgG; C-reactive protein